Computational techniques to solve electromagnetic problems by using FEM - (:unkn) unknown (My University, 2008)
Numerical modeling is nowadays an essential tool for all researchers involved with the field of electrical, mechanical engineering, physics and etc. The object of this paper is to provide a clear, easy and understandable study on FEM (finite element method) using MATLAB and MATHEMATICA, which both provide powerful support to solve large equations. 1D and 2D FEM solutions are studied on electromagnetic (EM) field distribution which is one of the essential parts of electrical engineering. The results from the two different programs were compared with those obtained by using the finite difference method (FD). Computer programs and formulations of the finite element technique have been constructed to make the concept more understandable and explicit for engineering students and practicing engineers.
Keywords: Electrostatic analysis; FD; FEM; Mathematica; MATLAB